Evaluation der Eingliederungseffekte von Arbeitsbeschaffungsmaßnahmen in reguläre Beschäftigung für Teilnehmer in Deutschland - Marco Caliendo; Reinhard Hujer; Stephan L. Thomsen (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
– This study evaluates the effects of job-creation measures (ABM) in Germany on the participants' individual integration into regular employment. An extensive and informative data set from the data stock of the Federal Employment Services (Bundesagentur für Arbeit - BA) is used for the study. This data set makes it possible to examine the effects of the schemes with a differentiation according to individual differences in the participants and taking the heterogeneous labour market structure into consideration. The data set contains information about all the ABM participants who started their schemes in February 2000 and about a control group of non-participants who were unemployed in January 2000 and did not enter the schemes in February 2000. With the aid of the information in the employment statistics it is possible here for the first time to examine the outflow into regular employment on the basis of administrative data. The study period ends in December 2002. Using matching methods the effects of job-creation measures are estimated with a regional differentiation and for particular problem and target groups of the labour market. The results show clear differences in the effects for sub-groups; all in all however, the empirical findings indicate that to a large extent it was not possible to meet the objective of integration into regular unassisted employment by means of job-creation measures.
Keywords: 330; Eingliederungsbilanz; Arbeitsbeschaffungsmaßnahme; Arbeitsbeschaffungsmaßnahme - Erfolgskontrolle; berufliche Reintegration; regionale Disparität; Teilnehmerauswahl; Qualifikationsniveau; Berufserfahrung; geschlechtsspezifische Faktoren; Langzeitarbeitslose; Zielgruppe; schwervermittelbare Arbeitslose; Rehabilitanden; Ausbildungsverzichter; IAB-Maßnahmeteilnehmergrunddatei; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland